Development of Islamic Education: The Multidisciplinary, Interdisciplinary and Transdisciplinary Approaches - Dina Mardiana; Abd. Rahim Razaq; Umiarso Umiarso (Al-Hayat: Journal of Islamic Education, 2020)
In the ideal level, Islamic education must touch on 3 (three) aspects. "Knowing" realm understanding value Islamic religion, "doing" realm practicing the values Islamic religion, "being" go through a period of life following values Islamic religion. However, the development of the 21-st Century, which provides open access to all information from cyberspace, has not been fully implemented in the field of Islamic education so that it gives a challenge for the world of Islamic education in implementing the concept of "being" optimally in the process of learning. This article aims to describe and analyze the development of the Islamic education curriculum through 3 (three) approaches: multidisciplinary, interdisciplinary, and transdisciplinary. This article uses a qualitative approach to the type of literature study research. A literature study that is in line with the research theme leads this research to the conclusion. First, the Common Core State Standards (Kurikulum Inti) emerge as a form of balance standardization between the aspects of ideal learning and skills needs in the 21st-century. Second, the difference between multidisciplinary, interdisciplinary, and transdisciplinary approaches lies in the "starting point" of each approach. Multidisciplinary emerge as the form of concepts and skills desired by each discipline (explicitly), interdisciplinary in the form of shared concepts and skills, as long as a scientific discipline (implicitly) and transdisciplinary in the form of real reality in life where students being both subject and object in gaining that knowledge. Third, the similarity between multidisciplinary, interdisciplinary and transdisciplinary approaches lies to balance between accountability, relevance, and development of the 21st-century; all three are integral parts of the Core Curriculum; all three involve more than one scientific discipline in discussing a theme/issue and; all three have aspects of evaluation/assessment during the learning process.